Detectores Multiusuários para DS/CDMA Canceladores de Interferência10.14209/jcis.2001.14 - Abrao e Paul, Taufik; E. Jeszensky, Jean (Journal of Communication and Information Systems, 2015)
This work makes a revision of the main suboptimal multiuser detectors (MUD) for DS-CDMA systems (Direct Sequence -Code Division Multiple Access). In this second part Interference Cancellation detectors (IC) are focused. Within various MUD, IC detectors result in optimum tradeoff performance x complexity, being shown a feasible option in the implementation of cellular systems for third generation (3G); in compensation interference cancellation demands accurate estimation of the channel parameters (received amplitude, delay and phase). Multiuser detectors are capable to operate under the effect of near-far (NFres) and they combat the multiple access interference (MAl), resulting in performance improvement in relation to the Conventional detector.